Memory in Drag : Historical and Sexual Strategies in Tomás Gutiérrez Alea’s Memories of Underdevelopment - Williams, Bruce (Cinémas)

(untitled) (Cinémas, 1998)
ABSTRACTRendered a true fetish of stagnation by the death of Cuba's bourgeois regime, the body of the male protagonist of Tomás Gutiérrez Aléa's Memories of Underdevelopment becomes a locus onto which the sexual strategies of the film debunk the contradictions implicit in moments of historical change.